Chlorin e6 Phospholipid Delivery System Featuring APN/CD13 Targeting Peptides: Cell Death Pathways, Cell Localization, In Vivo Biodistribution - Yulia A. Tereshkina; Lyubov V. Kostryukova; Elena G. Tikhonova; Yulia Yu. Khudoklinova; Nadezhda A. Orlova; Alisa M. Gisina; Galina E. Morozevich; Pavel A. Melnikov; Vadim S. Pokrovsky (MDPI AG, 2022)
We have previously designed a phospholipid delivery system for chlorin e6 to increase the efficacy of photodynamic therapy involving a second-generation photosensitizer. Further research into the matter led to double modification of the obtained nanoparticles with ligands exhibiting targeting and cell-penetrating effects: an NGR-containing peptide and heptaarginine (R7), respectively. This study investigated the cell death pathway on HT-1080 tumor cells after treatment with the proposed compositions: the chlorin e6 phospholipid composition and the two-peptide chlorin e6 phospholipid composition. It was demonstrated that most of the cells died by apoptosis. Colocalization analysis of chlorin e6 in the phospholipid composition with two peptides showed mitochondria are one of the targets of the photosensitizer. An HT-1080 tumor-bearing mouse model was used to evaluate the biodistribution of the drug in tumor, liver, and kidney tissues after administration of the study compositions in comparison with free chlorin e6. The photosensitizer mostly accumulated in the tumor tissue of mice administered the phospholipid compositions, and accumulation was increased 2-fold with the peptide-containing composition and approximately 1.5-fold with the unenhanced composition, as compared with free chlorin e6. The enhancement of the chlorin e6 phospholipid composition with targeting and cell-penetrating peptides was found to be effective both in vitro and in vivo.